2014
DOI: 10.1007/s00403-014-1527-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the IL-31 pathway in Mycosis fungoides and Sézary syndrome

Abstract: IL-31, predominantly produced by CD45RO + CLA + Th2 cells, plays an important pathogenetic role in pruritic skin diseases like atopic dermatitis. As tumor cells in Sézary syndrome (SS) and Mycosis fungoides (MF) possess similar immunophenotypes and the conditions mentioned are often associated with pruritus, the analysis of the IL-31 pathway in MF/SS patients is of interest. Serum samples from the peripheral blood of 23 patients and 17 controls were analyzed for IL-31 abundance and correlated with disease stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 32 publications
9
31
0
Order By: Relevance
“…Although several recent studies have found increased levels of IL-31 in CTCL, these studies largely focus on serum analysis and do not address the crucial question of IL-31's role in the skin (13,14,18). This is the first study to show the expression levels and patterns of IL-31 and both of its receptors within the skin of CTCL subjects with pruritus.…”
Section: Discussionmentioning
confidence: 98%
“…Although several recent studies have found increased levels of IL-31 in CTCL, these studies largely focus on serum analysis and do not address the crucial question of IL-31's role in the skin (13,14,18). This is the first study to show the expression levels and patterns of IL-31 and both of its receptors within the skin of CTCL subjects with pruritus.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent findings contradicted those from early studies. Möbs et al . found no difference in IL‐31, IL‐31RA, and OSMRβ expression among various stages of MF/SS.…”
Section: Resultsmentioning
confidence: 97%
“…These studies, although, only analysed IL‐31 and IL‐31 receptor levels in the serum . These interleukins are also quantifiable within the skin, and IL‐31RA and OSMRβ are present in keratinocytes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations